Empowering workers’ involvement: Unveiling the dynamics of communication, recognition, productivity, and decision-making in the RMG sector - Hawlader, Md. Rasel; Rana, Md. Masud; Kalam, Abul; Polas, Mohammad Rashed Hasan (Journal of Sustainable Tourism and Entrepreneurship, 2022)
Purpose: This study investigates the relationship between workers' perspectives on communication, recognition, productivity, and their involvement in the Readymade Garment (RMG) sector policymaking. Research Methodology:  A sample of 226 individuals from the RMG sector in Bangladesh was surveyed using a well-designed questionnaire. The data were examined, and the study's hypotheses were tested, using the statistical program SPSS V.25. In IBM SPSS, the chi-square test and other statistical techniques were used to examine the data. The study investigates the relationship between the independent variables, including communication, employee recognition, and productivity, and the dependent variable, worker perception, using a conceptual framework. Results: There is a positive and significant relationship between employees' perceptions of communication and their involvement in the decision-making process. The study also shows that there is a positive and significant association between workers' perceptions of employee recognition, productivity, and involvement in decision-making in Bangladesh's RMG industry. Additionally, the organization's decision-making process is significantly impacted by employee participation. Limitations: While many studies examined the workers’ participation in decision-making in the various sectors, only a few studies have focused on the RMG sectors to explore the effects of communication, employee recognition, and productivity on the workers’ participation in decision-making. Contributions: The study reveals that the organization’s total effectiveness is reflected in how deeply workers are involved in decision-making. The degree of involvement is a key determining element since encouraging people to engage instead of just dragging them along is essential for enhancing performance and ensuring commitment.